Earthquake Impact on Active Margins: Tracing Surficial Remobilization and Seismic Strengthening in a Slope Sedimentary Sequence. Issue 11 (12th June 2019) - Molenaar, Ariana; Moernaut, Jasper; Wiemer, Gauvain; Dubois, Nathalie; Strasser, Michael
Abstract: Strong earthquakes at active ocean margins can remobilize vast amounts of surficial slope sediments and dynamically strengthen the margin sequences. Current process understanding is obtained from resulting event deposits and low‐resolution shear strength data, respectively. Here we directly target a site offshore Japan where both processes are expected to initiate, that is, at the uppermost part (15 cm) of a sedimentary slope sequence. Based on a novel application of short‐lived radionuclide data, we identified, dated, and quantified centimeter‐scale gaps related to surficial remobilization. Temporal correlation to the three largest regional earthquakes attest triggering by strong earthquakes ( M w >8). Also, extremely elevated shear strength values suggest a strong influence of seismic strengthening on shallow sediments. We show that despite enhanced slope stability by seismic strengthening, earthquake‐induced sediment transport can occur through surficial remobilization, which has large implications for the assessment of turbidite paleoseismology and carbon cycling at active margins. Plain Language Summary: During strong earthquakes, large amounts of sediment are stripped from ocean slopes and transported into the deeper basin. The resulting event deposits can provide information on the recurrence of past earthquakes, which is crucial for seismic hazard assessment. To unravel the information stored within this archive, it is important to understand the effect of earthquakes on surficial slope sediments where the removal of sediment is supposed to take place. We discovered—for the first time—several centimeter‐scale gaps in a slope sequence offshore Japan, which can be linked to the largest regional earthquakes. Also, we found that seismic shaking can strengthen and stabilize a slope, therefore reducing the probability for large landslides and associated destructive tsunamis. This study shows that strong earthquakes can both stabilize and remobilize young sediments at ocean slopes. Key Points: Slope stratigraphy reveals direct impact of strong earthquakes on young sediments of the active margin offshore Japan Remobilization of surficial slope sediments at site occurs during M w 8+ earthquakes, allowing turbidite paleoseismology in terminal basins Seismic strengthening is most effective on uppermost sediments, progressively reducing submarine landslide potential